Grain-Size Prediction Model in Aluminum Castings Manufactured by Low-Pressure Technology - Fernández-Calvo, Ana Isabel; Lizarralde, Ibon; Sal, Elisa; Rodriguez, Patxi; Ochoa de Zabalegui, Edurne; Cia, Igor; Rios, Ariane (Journal of Casting & Materials Engineering, 2019)
The grain refinement in a real casting manufactured by Low Pressure Die Casting (LPDC) such as wheels and steering knuckles depends on the grain-refinement potential of the metal and the geometry of the part/process parameters. For this study, the effect of the cooling rate on the AlSi7Mg alloy with different metal qualities in terms of grain refinement was tested. The grain size has been metallographically evaluated in cylindrical test pieces and in the real wheels and steering knuckles manufactured at the Mapsa and Fagor Ederlan foundries. The Thermolan®-Al system has been used to evaluate the nucleation potential in terms of grain size on a standard cup. The grain size has been modeled taking into account the effect of the cooling rate measured in the center of the cylindrical test parts and the different grain-size potential. Different grades of refinement have been tested. The grain size measured in a real casting (wheel and steering knuckle) was used to calibrate the model for a real part in LPDC for different grain-size potential.